2011
DOI: 10.1007/s10964-011-9726-7
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of Loneliness and Depressive Symptoms Across Adolescence: Exploring the Role of Personality Traits

Abstract: Based on current theories of depression, reciprocal links between loneliness and depressive symptoms are expected to occur. However, longitudinal studies on adolescent samples are scarce and have yielded conflicting results. The present five-wave longitudinal study from mid- to late adolescence (N=428, M age at T1=15.22 years; 47% female) examined the direction of effect between loneliness and depressive symptoms, using cross-lagged path analysis. In addition, the robustness of these prospective associations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
168
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(189 citation statements)
references
References 57 publications
17
168
0
2
Order By: Relevance
“…This current study highlights the need for intervention research aimed at helping adolescents who experience chronic loneliness. Parents and school counsellors should be attentive to signs of chronic loneliness in their children or students before it evolves into serious bouts of depression (Vanhalst et al, 2012). Prevention programs that emphasise the promotion of family connectedness and school-based interventions that facilitate the development and maintenance of meaningful relationships over time, offer great potential in reducing adolescent's social isolation and are likely to yield longterm psychological benefits (Hall-Lande et al, 2007;Jose et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This current study highlights the need for intervention research aimed at helping adolescents who experience chronic loneliness. Parents and school counsellors should be attentive to signs of chronic loneliness in their children or students before it evolves into serious bouts of depression (Vanhalst et al, 2012). Prevention programs that emphasise the promotion of family connectedness and school-based interventions that facilitate the development and maintenance of meaningful relationships over time, offer great potential in reducing adolescent's social isolation and are likely to yield longterm psychological benefits (Hall-Lande et al, 2007;Jose et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The question of whether relationships among adolescents' loneliness and depressive symptoms are moderated by gender is interesting and germane. Although adolescent females tend to self-report higher levels of loneliness and depressive symptoms, some studies report that the strengths of the association between loneliness and depressive symptoms are similar for boys and girls Olsson et al, 2013;Vanhalst et al, 2012). In their studies with the elderly, Cacioppo, Hughes et al (2006) found that the association between loneliness and depressive symptoms was strong and significant for both males and females, but the association was significantly stronger for males.…”
Section: Overview Of Findings Within the Context Of The Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Feeling lonely is consequential for individuals and has been identified as a predictor of a broad array of health-related outcomes including objective health risk factors (e.g., elevated blood pressure, elevated number of inflammatory markers; Hawkley, Burleson, Berntson, & Cacioppo, 2003;Hawkley, Thisted, Masi, & Cacioppo, 2010;Shankar, McMunn, Banks, & Steptoe, 2011), health-relevant behaviors (e.g., smoking, physical inactivity, excessive alcohol consumption; Åkerlind & Hörnquist, 1992;DeWall & Pond, 2011;Hawkley, Thisted, & Cacioppo, 2009;Lauder, Mummery, Jones, & Caperchione, 2006;Shankar et al, 2011), and depression (Cacioppo, Cacioppo, Hughes, Waite, Hawkley, & Thisted, 2006;Qualter, Brown, Munn, & Rotenberg, 2010;Russell, Cutrona, Rose, & Yurko, 1984;Vanhalst et al, 2012).…”
mentioning
confidence: 99%